Petits riens sophocléens : Antigone IV: (v. 773–777, 795–802, 857–861, 883–888, 902–903, 925–928, 955–961, 970–976, 1019–1022, 1029–1030, 1033–1039, 1039–1043, 1074–1076) - Liberman, Gauthier (Hyperboreus, 2024)
This is the fourth of ﬁve sets of text-critical, exegetical and sometimes metrical remarks on Antigone. These *Sophocleuncula are not only minute philological notes but they involve broader issues having a bearing on the interpretation and meaning of the drama as a whole. These remarks were composed with a view to drawing attention to a number of forgotten or unseen diﬃculties and to trying to address a number of seen but unsolved problems more eﬃcaciously. The text and meaning of not a few other passages from other works of Sophocles or of other writers are also dealt with.